Planos de marketing vinculados a causas sociais: um estudo de caso - Oliveira, Stefan Krawczenko Feitoza de (2007)
The issue that triggered the research in this study was the current phenomen in which organizations look for a new marketing model, which aims to stop with the equalization of competitive factors, and consequently agregate value for their products and brands. As part of this issue, there are some questions still not clarified. The objective of this study is discussing how these marketing plans ad value to companies and their product. This objective was research via the revision of consumer behavior, cause related marketing and marketing planning theories, and via the discussion of a case study. This case study analysed the experience of a cause related marketing effort done by the Pampers brand. This case concluded that this marketing plan added value to the company by improving its brand equity, thru the creation of an emotional bond with consumer, on top of already existent association with consumers via brands functional benefits. Beyond that, the case study concluded that cause-related marketing plans are triggered and developed as it happens with traditional marketing plans. These plans are triggered based on a deep understanding of opportunitites and threats of market environment, and they use tools of marketing mix to reach their objectives and strategies, which are developed in the regular marketing planning process. Aditionally, the case study assessed that the supported social cause was set as key element of the marketing mix, influencing the brand positioning and communication, once in these marketing efforts the cause endorsement and the related social institution became part of brand promisses to consumers. It s important to highlight, that the case study has limitations given that it does not allow any generalization of its conclusions. Therefore, it is suggested replication of equal case studies in order to potentially confirm its results